1999
DOI: 10.1159/000024188
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Olea europaea Pollen and Relation with Clinical Findings

Abstract: Background: Olea europaea pollen is an important cause of seasonal allergic rhinitis and bronchial asthma in southern Spain. For patients allergic to grass pol– len the critical concentration of airborn pollen is 50 grains/m3, but in the case of Olea pollinosis no data is available. Methods: Fifty–six seasonal allergic rhinitis patients (29 in 1994 and 27 in 1995) were included in this study, all of whom lived in Jaen. Daily symptom card were filled in and pollen counts during May and June were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 11 publications
2
44
0
2
Order By: Relevance
“…Moreover, pollen from the olive groves situated in Jaen and Granada provinces (Fig. 1), which is usually emitted later in the season, are scarcely represented in the Córdoba olive pollen data (Florido et al, 1999;Vázquez et al, 2002). The total pollen emitted into the atmosphere can be used as an representative index, of the floral phenology from different cultivars and areas; by this means, airborne pollen concentration due to re-flotation can be excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, pollen from the olive groves situated in Jaen and Granada provinces (Fig. 1), which is usually emitted later in the season, are scarcely represented in the Córdoba olive pollen data (Florido et al, 1999;Vázquez et al, 2002). The total pollen emitted into the atmosphere can be used as an representative index, of the floral phenology from different cultivars and areas; by this means, airborne pollen concentration due to re-flotation can be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Although aerobiological studies have been traditionally applied to allergy research (Domínguez et al, 1993;Florido et al, 1999), today their usefulness is being shown for crop forecasting. Annual pollen Field Crops Research 86 (2004) [43][44][45][46][47][48][49][50][51] emission is a measure of the quality of the season and can thus be used as a bio-indicator of fruit production.…”
Section: Introductionmentioning
confidence: 99%
“…Ad -Andujar, Al -Alcala la Real, Jn -Jaen. Florido et al, 1999;Díaz de la Guardia et al, 2003;d'Amato et al, 2007). A series of studies have revealed that production and viability of these olive groves depend heavily on, among other things, the cultivar of the olive tree, which sometimes presents cases of male sterility (Rapoport, 2008).…”
Section: Abstract: Environmental Effect Flower Production Rate Micrmentioning
confidence: 99%
“…Olive pollen induces mainly nasal and conjunctival symptoms (14), although it may also induce asthma exacerbations in areas with high antigenic load. Our patients were from Andalusia, a region in southern Spain with particularly high pollen counts during the pollen season (5,000 grains/m' with peaks reaching more than 10,000 grains/m-) and a high prevalence of asthma (15). We previously described specific genetic and environmental factors associated with olive pollen allergy (16)(17)(18)(19)(20).…”
Section: I721-727x (2012)mentioning
confidence: 99%